Knowledge and Attitudes on Fetal Anomalies among Pregnant Women in Teaching Hospital Mahamodara, Galle - K.T.G. Kanchana; P. Youhasan (Intelektual Pustaka Media Utama, 2018)
Fetal anomalies significantly contribute towards neonatal mortality worldwide. In Sri Lanka major cause for neonatal deaths is fetal anomalies 41%. A Descriptive cross-sectional study was conducted in Antenatal clinic, Teaching Hospital, Mahamodara. An interviewer-administered, pretested questionnaire was used. Hundred and fifty pregnant women participated in this study. Majority; 105 (70%) were found in the age of below 30 years, and 80 (53.3%) educated up to G.C.E. Ordinary Level. 83 (53.3%) were multigravida and 93(62%) were planned pregnancies. Higher proportion of the participants; 92(61%) , 88(56.7%) and 123(82%) had good knowledge on the risk factors, pre conception care and on preventive actions related to birth defects respectively. Significant proportion (26.7%) had poor knowledge regarding birth defects. There are 143 (95.3%) of the participants interested to know more information on birth defects, 72% believed birth defects were due to evil spirits. Even though 52% of women did not want to terminate their pregnancy if they had a fetus with anomalies, 80.7% of them opined that the termination of pregnancy with birth defected should be legalized. The educational level, parity and planning of current pregnancy of the participants were significantly correlated (p < 0.05) with their knowledge on pre conception care, preventive actions, knowledge on risk factors on birth defects.